The ATP‐binding cassette transporter subfamily C member 2 in Bombyx mori larvae is a functional receptor for Cry toxins from Bacillus thuringiensis. (14th March 2013) - Tanaka, Shiho; Miyamoto, Kazuhisa; Noda, Hiroaki; Jurat‐Fuentes, Juan Luis; Yoshizawa, Yasutaka; Endo, Haruka; Sato, Ryoichi
<x xml:space="preserve">Abstract</x> Bacillus thuringiensis is the most widely used biopesticide, and its Cry toxin genes are essential transgenes for the generation of insect‐resistant transgenic crops. Recent reports have suggested that ATP‐binding cassette transporter subfamily C2 (ABCC2) proteins are implicated in Cry intoxication, and that a single amino acid insertion results in high levels of resistance to Cry1 toxins. However, there is currently no available direct evidence of functional interactions between ABCC2 and Cry toxins. To address this important knowledge gap, we investigated the role of Bombyx mori ABCC2 (BmABCC2) or its mutant from a Cry1Ab‐resistant B. mori strain on Cry1A toxin action. When we expressed BmABCC2 ectopically on Sf9 cells, it served as a functional receptor, and the single amino acid insertion found in BmABCC2 from Cry1Ab‐resistant larvae resulted in lack of susceptibility to Cry1Ab and Cry1Ac. Using the same expression system, we found that Bo. mori cadherin‐like receptor (BtR175) conferred susceptibility to Cry1A toxins, albeit to a lower degree than BmABCC2. Coexpression of BtR175 and BmABCC2 resulted in the highest cell susceptibility to Cry1A, Cry1F, and even the phylogenetically distant Cry8Ca toxin, when compared with expression of either receptor alone. The susceptibility observed in the coexpressing cells and that in Bo. mori larvae are likely to be correlated, suggesting that BtR175 and BmABCC2 are important factors determining larval susceptibility. Our study demonstrates, for the first time, Cry toxin receptor functionality for ABCC2, and highlights the crucial role of this protein and cadherin in the mechanism of action of Cry toxin.